(untitled) (International Journal of Engineering and Computer Science, 2017)
Employing an efficient processing technique is considered as an essential step to improve the overall visual representation of clinical images, and as a consequence provides better diagnosis results. This paper employs an easy, fast and reliable technique to detect cancerous tissue in bone by using different image processing techniques such as contrast enhancement, edge detection and image fusion. The experimental results show, the proposed method could obtain the smooth image with edge showing the disease affected part without the spatial and spectral noise